Growing The Value of Islamic Religious Education to Prevent Bullying Behavior in Islamic Boarding Schools - Suryadi Suryadi; A Faridul Ilmi; Sukamto Sukamto (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Bullying is aggressive behavior that often occurs in the community, especially in Islamic boarding schools and schools. This was done because he considered himself superior and his juniro was considered weak and made him a victim. Bullying is an act or attitude that makes other people hurt, this action is carried out by a person, two or a group, repeated over a long period of time by insulting, ridiculing, hitting, swords. Bullying is a global problem that can occur in all educational institutions, including Islamic boarding schools. Bullying in Islamic boarding schools occurs in physical, verbal and social forms, caused by internal and external factors. Bullying has many very negative impacts on the perpetrators or victims, both in terms of individual, social and academic life. This article aims to find out the types, forms, factors, and efforts to prevent bullying in Islamic boarding schools in Indonesia. This article uses qualitative research methods. The data used comes from various journals, books, journals, as well as the results of studies related to bullying in educational institutions. The data analysis technique used is Miles' qualitative data analysis technique. namely data condensation, data presentation, and drawing conclusions. The results of the study show that bullying in Islamic boarding schools occurs in physical, verbal and social forms, which are generally caused by internal and external factors. Bullying has many negative impacts both on the part of the perpetrators and on the part of the victims of bullying themselves, both in terms of individual, social and academic life.